Dynamics of Social Relationships and the Role of Counseling Guidance in Improving the Emotional Well-Being of Gen Z Students in the Boarding House of the Al Bukhari Wesalo Islamic Education Management Perspective - Nurul Azizah; Muh. Ramadhan; Ade Saputra (Journal of Educational Sciences, 2026)
This study aims to explore the dynamics of social relationships and the role of counseling in improving the emotional well-being of students in the Gen Z era, specifically at the Al Bukhari Wesalo Islamic Boarding School. The background of this study is based on the increasing cases of mental health disorders among adolescents, with data from the 2023 Indonesian Mental Health Index showing 9,162,886 cases of depression. The method used is a qualitative approach with in-depth interviews and guided discussion forums (FGDs) involving students, counselors, and Islamic boarding school administrators. The results show that positive social interactions among students contribute significantly to their emotional well-being. Counseling plays a crucial role in providing emotional support and developing social skills. This study recommends the integration of more holistic counseling programs into Islamic education management to create an environment that supports students' emotional well-being. Thus, this research is expected to contribute to the development of educational policies that are more responsive to students' psychological needs in the modern era.